Modifying Hebbian Network for Text Cipher (Baghdad Science Journal, 2011)
The objective of this work is to design and implement a cryptography system that enables the sender to send message through any channel (even if this channel is insecure) and the receiver to decrypt the received message without allowing any intruder to break the system and extracting the secret information.This work modernize the feedforward neural network, so the secret message will be encrypted by unsupervised neural network method to get the cipher text that can be decrypted using the same network to get the original text.The security of any cipher system depends on the security of the related keys (that are used by the encryption and the decryption processes) and their corresponding lengths.In this work, the key is the final weights that are obtained from the learning process within the neural network stage, So the work can be represented as an update or development for using the neural network to enhance the security of text.As a result for a powerful design, the resulted cipher system provides a high degree of security which satisfies the data confidentially which is the main goal of the most cryptography systems.